Notes on Philippine divinities - Jocano, F. Landa ([No place of publication publisher not identified], 1968)
This paper is ethno-historical in nature. It is designed to put together representative pantheons of different Philippine divinities. The materials for the purpose have been gathered from historical documents, ethnographic monographs, and field observations conducted by the writer and other fieldworkers among different indigenous religious groups in the various parts of the country.
Fi-13673g donated Prof. Mamoru Tsuda, MA, UP 1977.
Keywords: God -- Folklore; Supernatural